Mao's images: artists and China's 1949 transition - Geng, Yan (J.B. Metzler, 2018)
Intro -- Table of Contents -- Preface -- 1. Chinese Art of The Early People's Republic: A Transitional Period -- 1.1 The Reform of Art Institutions -- 1.2 Popularization and Dissonance -- 1.3 Mao's Image and Its Implications -- 2. Mao Parade: Huang Jun and New Chinese Painting -- 2.1 The (Re)Invention of Guohua -- 2.2 Alternative Fang -- 2.3 Huang Jun and Xu Beihong's Guohua Reform -- 2.4 Mao's Image for the Labor Day Parade -- 2.5 Huang Jun's Popular Art and His Defense of Guohua -- 2.6 Conclusion -- 3. Mao On the Gate: Li Keran and the New Year Picture -- 3.1 New Nianhua -- 3.2 Transmedia and Transformation of Li Keran's Guohua -- 3.3 Propaganda: The Political and the Social -- 3.4 Adding Mao's Image to Beipai Park -- 3.5 From Actual Scene to Scenic Landscape -- 3.6 Conclusion -- 4. Hidden Mao: Gu Yuan and Communist Woodcut -- 4.1 Modern Woodcut -- 4.2 Creating Images of a Picturesque Yan'an -- 4.3 A "Painful" Change After 1942 -- 4.4 The Korean War and Gu Yuan's Two Versions of Mao -- 4.5 When Woodcut (Muke) Became Printmaking (Banhua) -- 4.6 Conclusion -- 5. Dual Mao: Dong Xiwen and National Oil Painting -- 5.1 From Oil Painting to Xihua -- 5.2 Reinventing a Cultural Frontier -- 5.3 Dong Xiwen's Turn to the Communist Party -- 5.4 Mao at His Inaugural Ceremony -- 5.5 Nationalizing Oil Painting: A Voice in Protest -- 5.6 Conclusion -- 6. Epilogue: More Than an Image of Mao -- References -- Chinese Names and Terms -- Index.